Chromosome numbers in insects of Argentina I. Cytogenetic characterization of 15 species with economic importance. (2020)
In the present study, the somatic and gametic chromosome numbers in fifteen species of insects from Argentina are reported. Said species are characterized for their economic importance as pest of crops or as agricultural pest controllers. The species belonged to the following orders and families: Neuroptera, Chrysopidae: Ceraeochrysa cincta (n = 5 + XY), Ceraeochrysa paraguaria (n = 5 + XY), Chrysoperla argentina (n = 5 + XY), Chrysoperla asoralis (n = 5 + XY), Chrysoperla externa (n = 5 + XY), Leucochrysa cruentata (n = 7 + XY) y Plesiochrysa elongate (n = 5 + XY), Coleoptera, Coccinellidae: Cyclonela sanguinea (n = 9 + XYp), Eriopis connexa (n = 9 + XYp), Harmonia axyridis (n = 7 + XYp), Hippodamia convergens (n = 9 + XYp), y Melyridae: Astylus atromaculatus (n = 8 + XYp), Dermaptera, Forficulidae: Doru lineare (2n = 20) and D. luteipes (2n = 20), Diptera, Ulidiidae: Euxesta eluta (n = 5 + XY). Chromosomal information for six species and additional gametic chromosome number for Euxesta eluta are established for the first time. In addition, a new chromosome number is cited for Astylus atromaculatus that is different to the one previously reported.